Comparative assessment of downstream processing options for lactic acid - Joglekar, H. G.; Rahman, Imran; Babu, Suresh; Kulkarni, B. D.; Joshi, Ajit (Separation and Purification Technology, 2006)
The possibility of manufacturing a biodegradable polymer from lactic acid has led to extensive research in recovery of lactic acid produced by fermentation, by different downstream processing routes. This paper assesses the suitability of different downstream processing options such as reactive extraction, adsorption, electrodialysis, esterification and reactive distillation. It compares the costs of different process routes. The assessment indicates that the conventional precipitation of calcium lactate, followed by acidification, esterification and hydrolysis will be the most economical route although it generates large quantity of gypsum sludge. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; electrodialysis; Esterification; Lactic acid; Reactive distillation; reactive extraction

Reverse microemulsion mediated sol-gel synthesis of lithium silicate nanoparticles under ambient conditions: Scope for CO2 sequestration - Khomane, Ramdas B.; Sharma, B. K.; Saha, S.; Kulkarni, B. D. (Chemical Engineering Science, 2006)
We report on the synthesis of nanocrystalline lithium silicate by coupling of sol-gel method in reverse microemulsion. The sample calcined at 800 degrees C gives pure phase lithium metasilicate nanocrystallites. X-ray diffraction and transmission electron microscopy confirmed the formation of nanocrystalline lithium silicate particles with a narrow size distribution. The nanoparticle prepared in the microemulsion shows enhanced CO2 sorption capacity and shorter retention times at higher temperature (similar to 131 ml/g at STP at 610 degrees C which are better than the best known results. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; Carbon dioxide; Microemulsion; particle; separations; sol-gel; surfactant